Global software development agile planning model: challenges and current trends - Hajar Lamsellak; Mohammed Ghaouth Belkasmi (Institute of Advanced Engineering and Science, 2023)
Agile planning offers a number of benefits that make the customers active members of the team throughout the project. In global software development (GSD), geographic separations demand special attention to harness these benefits. Our paper conducted a systematic mapping study (SMS) to analyze GSD-specific agile planning challenges followed by a systematic literature review (SLR) for efficient solutions. These studies led to a model for agile planning in global software development supporting GSD practitioners during this process.